Fischer's base-triggered formal (3+2) cycloadditions with 3-isothiocyanato oxindoles as acceptor–donor synthons. Issue 31 (29th March 2023) - Liu, Xiong-Wei; Chen, Zi-Yue; Liu, Ren-Ming; Zhang, Wen-Hui; Pan, Bo-Wen; Zhou, Jian; Tian, You-Ping; Zhou, Ying; Liu, Xiong-Li
Abstract : Examples of Fischer's base-triggered (3+2) cycloadditions and expanding the applicability scope of 3-isothiocyanato oxindoles. Abstract : Herein, previously unreported Fischer's base reactants serving as useful 2C building blocks in (3+2) cycloaddition reactions to build a library of bispiro[Fischer's base-oxindole] hybrids are described. These structurally intriguing products containing three adjacent quaternary stereocentres were smoothly afforded in up to 82% yield and >20 : 1 dr under catalyst-free conditions. Notably, the present protocol firstly employs 3-isothiocyanato oxindole serving as an acceptor and then as a donor in the formal (3+2) cycloadditions, allowing practical, straightforward access to structurally diverse cycloadducts. This work expands the applicability scope of 3-isothiocyanato oxindoles, which have been limited to behaving as donor/acceptor-based synthons in cycloadditions in previous work.